The life of the Virgin - Maximus, Confessor, Saint, approximately 580-662 (Yale University Press, 2012)
Long overlooked by scholars, this seventh-century Life of the Virgin, attributed to Maximus the Confessor, is the earliest complete Marian biography. Originally written in Greek and now surviving only in Old Georgian, it is now translated for the first time into English. It is a work that holds profound significance for understanding the history of late ancient and medieval Christianity, providing a rich source for understanding the history of Christian piety. This Life is especially remarkable for its representation of Mary's prominent involvement in her son's ministry and her leadership of the early Christian community. In particular, it reveals highly developed devotion to Mary's compassionate suffering at the Crucifixion, anticipating by several centuries an influential medieval style of devotion known as #x1C;affective piety#x1D.